Literasi Iklan Digital Edukasi Anti Pembelian Impulsif Siswa-Siswi SMK Puspita Husada - Sandra Olifia; Herik Kurniawan (Jurnal Pustaka Dianmas, 2026)
This Community Service activity aims to improve digital advertising literacy and build anti-pembelian impulsif awareness among students of SMK Puspita Husada, South Tangerang. This program is motivated by the increasing exposure to digital advertising through social media that utilizes algorithms, influencers, hidden endorsements, and various persuasive strategies that have the potential to encourage adolescent consumer behavior. As active users of digital media, adolescents are a group vulnerable to impulsive buying behavior due to the influence of trends, Fear of Missing Out (FOMO), and the need for social recognition. The activity was carried out through counseling methods, lectures, interactive discussions, and sharing sessions involving lecturers and students of the Communication Studies Program at Pamulang University. The material provided covered media literacy, advertising literacy, persuasive strategies in digital advertising, consumer behavior, and wise financial management. The results of the activity showed an increase in participants' understanding of various forms of persuasion in digital advertising, such as flash sales, fake testimonials, crossed-out prices, and the use of buzzers. In addition, participants demonstrated a more critical awareness of commercial content in digital media and the importance of distinguishing needs from wants. This activity contributes to strengthening digital literacy among teenagers to be more critical, rational, and responsible in facing consumer culture in the digital era.